Pathogenic Effect of Prevotella intermedia on a Mouse Pneumonia Model Due to Methicillin-Resistant Staphylococcus aureus With Up-Regulated α-Hemolysin Expression - Yamashita, Yu; Nagaoka, Kentaro; Kimura, Hiroki; Suzuki, Masaru; Fukumoto, Tatsuya; Hayasaka, Kasumi; Kaku, Norihito; Morinaga, Yoshitomo; Yanagihara, Katsunori; Konno, Satoshi (Frontiers in Microbiology, 2020)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a common causative agent of pneumonia; however, the detailed mechanism underlying severe MRSA pneumonia, including association with oral hygiene or periodontitis, remains poorly characterized. In this study, we examined the pathogenic effect of Prevotella intermedia, a major periodontopathic pathogen, on MRSA pneumonia. Methods: The pathogenic effect of the supernatant of P. intermedia (Pi Sup) was investigated in a murine MRSA pneumonia model, using several clinical strains; whereas the bactericidal activity of polymorphonuclear leukocytes (PMNs) was investigated in vitro. The effect of Pi Sup on mRNA expression of the toxin/quorum sensing system (rnaIII) was investigated by quantitative reverse transcription PCR both in vitro and in vivo. Results: Mice infected by hospital-acquired MRSA (HA-MRSA) with Pi Sup exhibited a significantly lower survival rate, higher bacterial loads in the lungs, and higher α-hemolysin (hla) expression in the lungs, than those without Pi Sup. A similar effect of Pi Sup was not observed with MRSA strains producing Panton-Valentine leucocidin or toxic shock syndrome toxin. In vitro, Pi Sup suppressed bactericidal activity of PMNs against the HA-MRSA strain. HA-MRSA was the clinical strain with the highest ability to proliferate in the lungs and was accompanied by time-dependent up-regulation of rnaIII and hla. Conclusions: Our results provide novel evidence that the product of P. intermedia exerts a pathogenic effect on MRSA pneumonia, in particular with a strain exhibiting strong proliferation in the lower airway tract. Moreover, our results indicate that P. intermedia affects MRSA toxin expression via quorum sensing in a strain-dependent fashion, which might be important for understanding the pathogenesis of severe MRSA pneumonia.